Normative framework for the development of entrepreneurship in Serbia from a gender perspective - Dokmanović, Mirjana (Teorija in praksa, 2026)
Despite efforts made by the Republic of Serbia to boost women’s entrepreneurship, gender gaps remain, including income discrepancies, access to resources and entrepreneurial knowledge, and the balancing of professional and private responsibilities. The aim of the article is to determine the extent to which national legislation is gender-responsive; namely, whether it addresses the unique challenges faced by women when starting and growing a business. Gender analysis is the primary method of this assessment, with findings showing the legislation still does not fully support women’s entrepreneurial activities. By being mainly gender-blind, in that it ignores gender differences concerning opportunities and resource allocation for women and men, the legislation does not contribute to developing a context that promotes women’s entrepreneurship. The mentioned goal would be achieved by introducing gender-transformative legislation that provides a clear definition of ‘women’s entrepreneurship’, ‘women-owned business’ and ‘women-led business’, engenders taxation and corporate regulation, and introduces measures which give support to women when launching and growing a business. Simultaneously, women entrepreneurs should be provided with the same maternity leave rights as those enjoyed by women who work for an employer.
Keywords: analiza spola; gender analysis; maternity leave; Podjetništvo; porodniški dopust; social entrepreneurship; social protection; socialna zaščita; socialno podjetništvo; Spolne vloge v delovnem okolju; women’s entrepreneurship; Ženske; žensko podjetništvo